Analisis Motivasi Belajar Siswa Kelas X IPS Pada Pembelajaran Sejarah Di SMA Santun Untan Pontianak - Pratiwi Juniar Putri; Astrini Eka Putri; Andang Firmansyah (Peneliti.net, 2023)
This research adopts a qualitative approach with a descriptive method to investigate the intrinsic and extrinsic motivations of X-grade Social Sciences students and identify obstacles in the history learning process. The study is conducted at Santun Untan Pontianak High School, located in Pontianak City, specifically at Jl Daya Nasional, Komp Untan, Bansir Laut, Pontianak Southeast District. The data collection techniques include observation, interviews, and documentation, utilizing observation guidelines, interview guidelines, and documentation as the tools. Data analysis involves data reduction, presentation, and inference. The findings reveal that the intrinsic and extrinsic learning motivations of X-grade Social Sciences students are influenced by the abilities of both teachers and students. The research concludes that: 1) The intrinsic motivation of X-grade Social Sciences students demonstrates a lack of passion, desire for success, drive, and future aspirations in history learning. 2) The extrinsic motivation of X-grade Social Sciences students indicates that despite interesting learning activities, rewards, and a conducive learning environment, students are not adequately motivated. 3) The obstacles in the history learning process are primarily attributed to the insufficient facilities and infrastructure.